THE IMPACT OF QUALITY MANAGEMENT ON WASTE MANAGEMENT IN INDUSTRIAL KITCHENS - THE ORGANIC BIOTECH CASE STUDY - Defrein, Talita; Geiza dos Anjos, Andréa; Ottoni Zimmermann, Guilherme; Novais da Silva, Fernando (Revista Gênero e Interdisciplinaridade, 2025)
Food waste is a critical global and national challenge, as approximately one-third of all food produced worldwide is lost or wasted annually (Ferigollo; Busato, 2018; Belik, 2018). In 2019, about 17% of all food available for consumption was discarded across households, retail, and food service sectors (Chamarelli, 2021). In Brazil, the issue is particularly significant, with the country ranking 10th globally in food waste generation (Peixoto, 2017). Many companies still lack structured methods to quantify their waste. This article presents the waste management initiatives implemented by Organa Biotech in industrial kitchens in Santa Catarina. The company applies management methodologies, technological tools, and awareness programs to align operational efficiency with the United Nations Sustainable Development Goal (SDG) 12.3, which aims to halve global per capita food waste by 2030 (United Nations, 2025). Through data-driven management and visual awareness strategies, Organa demonstrates that adopting sustainable practices is both feasible and advantageous for reducing waste. This work was supported by the Fundação de Amparo à Pesquisa e Inovação do Estado de Santa Catarina (FAPESC), through Public Call Nº 50/2024 – Programa Impulsiona (SC).